Factors Related to Women's Quality of Life in The Climacteric Period - Nonik Ayu Wantini; Lenna Maydianasari; Jacoba Nugrahaningtyas Wahjunung Utami (STIKes Patria Husada Blitar, 2023)
Quality of life is satisfaction on the physical, psychological, social, and environmental aspects in the climacteric period. Climacterium is the period of life from decreased activity to the end of ovarian function, which has an impact on the occurrence of climacteric syndrome. The purpose of this study was to determine the factors associated with the quality of life of women during the climacteric period. This research method was an analytical survey, with a cross-sectional design. The research was conducted in August 2022 at Padukuhan Karangnongko, Tirtomartani, Kalasan, Sleman. A sample of 90 people was selected by proportional random sampling. The research instrument used the WHOQOL-BREF questionnaire, data analysis used Kendall Tau. Factors that are not related to women's quality of life include age, education, occupation, parity, history of chronic disease, history of breast and cervical cancer screening. Factors related to women's quality of life are health insurance (p-value = 0.005) and physical activity (p-value = 0.036). Health insurance should be prepared early, and regular physical activity can improve the quality of life for women during the climacteric period